2007
DOI: 10.2527/jas.2006-064
|View full text |Cite
|
Sign up to set email alerts
|

Breeding objectives for Targhee sheep1

Abstract: Breeding objectives were developed for Targhee sheep under rangeland production conditions. Traits considered were those for which EPD were available from the US National Sheep Improvement Program and included direct and maternal effects on 120-d weaning weight (WW and MM, respectively); yearling weight (YW); yearling fleece weight, fiber diameter, and staple length; and percent lamb crop (PLC), measured as the number of lambs born per 100 ewes lambing. A bioeconomic model was used to predict the effects of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…The traits of economic importance found here are in agreement with Borg et al (2007), Kosgey et al (2004) and Wolfová et al (2009) except for wool traits which are not important in this region of Brazil as generally sheep are not sheared. Most sheep selection indices involve wool traits, which make them difficult for comparison with data here.…”
Section: Resultssupporting
confidence: 91%
“…The traits of economic importance found here are in agreement with Borg et al (2007), Kosgey et al (2004) and Wolfová et al (2009) except for wool traits which are not important in this region of Brazil as generally sheep are not sheared. Most sheep selection indices involve wool traits, which make them difficult for comparison with data here.…”
Section: Resultssupporting
confidence: 91%
“…Other than Australia, New Zealand, and the United States (Borg et al, 2007), wool traits are of low importance in European countries (Conington et al, 2006;Krupová et al, 2009), which was also confirmed in our investigation. Therefore, these traits are often ignored in breeding goals.…”
Section: Economic Weights Of Traits For Suffolk Sires In Different Brsupporting
confidence: 91%
“…Krupová et al (2009) expressed the EV for growth rate of lambs till weaning per daily gain of female lambs born as singles. Borg et al (2007) chose ewe lambs born as singles and weaned at an age of 120 days as the reference category for the calculation of the EVs for birth and weaning weight. Groen (1988) defined a female calf born in a cow's first parturition as the reference category for the calculation of the EV for birth weight; cows were the reference category for mature weight.…”
Section: Definition Of Traits Expressed In Different Sexes or Animal mentioning
confidence: 99%